Spirulina platensis as a feed additive: impact on growth, oxidative status, and gene expression in Awassi lambs - Kanyaw I. Mahmud; Mohsin A. Ahmad; Dler A. Othman Al-Sherwany; Nawzad M. Aziz; Shahabuddin Gharahveysi; Karwan Y. Kareem (Journal of Kerbala for Agricultural Sciences, 2025)
The purpose of this research was to investigate whether Spirulina platensis (SP) had an impact on the growth performance, blood metabolism, antioxidant and oxidative status, MDA, and GPX-3 genes of Awassi male lambs. A total of 24 Awassi lambs (3.5-4 months) with an average initial weight of 27kg were used in the study. The lambs were divided into three groups: the control group fed a basal diet without SP supplementation, while the lambs in T1 and T2 were fed a basal diet supplemented with 2 and 3% SP, respectively. Lambs administered with 2% SP enhancement growth performance and increased carcass weight. It seems that 2% Spirulina supplementation significantly surpasses (P<0.05) those lambs fed control and 3% SP in daily gain in weight and had a lower feed conversion ratio. The levels of malondialdehyde decreased numerically in the liver and considerably (P<0.05) in the serum by supplementing Spirulina in the diet. Additionally, spirulina powder increased antioxidant capacity, which raised the liver and serum levels of GPX. While controlling the proportionate transcription of antioxidant genes, spirulina powder enhanced the proportionate amount of expression of genes linked to GPX-3's antioxidant activity by 3.068 times. It can be concluded that the 2% spirulina has a substantial effect on daily gain, immunity, antioxidant status, and carcass characteristics.